Analisis Teknik Dasar Bola Basket Peserta Ekstrakurikuler SMA Negeri 4 Lubuklinggau - Redo Mahendra; Wawan syafutra; Ahmad Gawdy Pranosa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the basic techniques of basketball in extracurricular participants at SMA Negeri 4 Lubuklinggau. This research uses a quantitative descriptive research design, using survey methods with test and measurement techniques. The population of this study was all students participating in the extracurricular activities at SMA Negeri 4 Lubuklinggau City in 2022, with a total sample of 14 people who were selected using a total sampling technique. The results of the research and data analysis showed that the basic basketball skills of extracurricular participants at SMA Negeri 4 Lubuklinggau City in 2022 were in the very poor category of 7.14% (1 athlete), the less category was 21.43% (3 athletes), the moderate category was 50.00% (7 athletes), good category of 7.14% (1 athlete), and very good category of 14.29% (2 athletes). In conclusion, the basic basketball skills of athletes participating in extracurricular activities at SMA Negeri 4 Lubuklinggau City in 2022, with an average score of 150.00, are included in the excellent category. Keywords: basic techniques, basketball, Skills,